Negotiating Terrains: Stories from the Making of “Siida” - Ekeland, Torun Granstrøm; Kramvig, Britt (Science & Technology Studies, 2013)
In this article we develop some arguments from a research project where the researchers were also participants in the making of a multiplayer online game. The “Siida” project emerged as a challenge to the static and monolithic vision of Indigenous Saami culture and history. It seeks to create an arena for learning founded on new approaches to research-based historical pedagogy. This involvement became the grounds from where we could refl ect upon what design is all about. We will argue that in order to work, design needs to relate to the specifi cities of place and be located as multiple practices. As a methodological tool for the analysis of partial connections between actors’ knowledge practices, we put the concept of material boundary metaphor to work. We tell the ethnographic story of a complex media production as an on-going negotiation between knowledge and technical design.